2021
DOI: 10.1038/s41380-021-01104-2
|View full text |Cite
|
Sign up to set email alerts
|

Altered network and rescue of human neurons derived from individuals with early-onset genetic epilepsy

Abstract: Early-onset epileptic encephalopathies are severe disorders often associated with specific genetic mutations. In this context, the CDKL5 deficiency disorder (CDD) is a neurodevelopmental condition characterized by early-onset seizures, intellectual delay, and motor dysfunction. Although crucial for proper brain development, the precise targets of CDKL5 and its relation to patients’ symptoms are still unknown. Here, induced pluripotent stem cells derived from individuals deficient in CDKL5 protein were used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 85 publications
3
42
0
Order By: Relevance
“…In further support of our findings, Negraes et al have found similar synaptic defects in iPSCs-derived cortical neurons from CDD patients (Negraes et al, 2021). In apparent contrast from our observation, they found an increased mGlurR5-PanHomer association in CDD human organoids (Negraes et al, 2021) while we revealed that mGluR5-Homer1bc binding, an association crucial for this receptor function, is decreased in CDKL5 mutant mice. The most parsimonious explanation of this discrepancy arises primarily either the different technical approaches or the experimental models used (i.e., mice brain vs CDD human organoids).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In further support of our findings, Negraes et al have found similar synaptic defects in iPSCs-derived cortical neurons from CDD patients (Negraes et al, 2021). In apparent contrast from our observation, they found an increased mGlurR5-PanHomer association in CDD human organoids (Negraes et al, 2021) while we revealed that mGluR5-Homer1bc binding, an association crucial for this receptor function, is decreased in CDKL5 mutant mice. The most parsimonious explanation of this discrepancy arises primarily either the different technical approaches or the experimental models used (i.e., mice brain vs CDD human organoids).…”
Section: Discussionsupporting
confidence: 92%
“…To properly function, mGluR5 requires binding with Homer1bc (Aloisi et al, 2017), a scaffolding protein that is severely downregulated in the cerebral cortex of both CDKL5 −/y mice and CDD patients (Pizzo et al, 2019, 2016; fig. 6A) as well as in iPSCs-derived neurons from CDD patients (Negraes et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Cortical organoids have been used in high-throughput screening platforms using calcium imaging as read-out to test the effect of novel therapeutic compounds ( Negraes et al, 2021 ). The use of both low- and high-throughput electrophysiological techniques, such as patch-clamping and MEAs respectively, will help to better characterize the effectiveness of novel treatments in normalizing pathological neuronal and network activity.…”
Section: Discussionmentioning
confidence: 99%
“…Over the course of 10 months, cortical organoids exhibited a steady increase in firing rate, burst frequency, synchronicity and population spiking. This cortical organoid model was used to investigate changes in network activity in organoids derived from patients with CDLK5-deficiency disorder (CDD), a neurodevelopmental disorder associated with early-onset epilepsy ( Olson et al, 2019 ; Negraes et al, 2021 ). MEA recordings showed consistent increases in electrical activity in CDD-derived cortical organoids compared to controls, as well as a significant increase in mean firing rate and network synchronicity early in development ( Negraes et al, 2021 ).…”
Section: Cellular and Network Electrophysiological Properties Of Huma...mentioning
confidence: 99%
“…This is of particular interest for diseases that involve abnormal excitability such as epilepsy. This was exemplified in a study by Negraes and collaborators, who conducted a phenotypic and target agnostic assay monitoring spontaneous calcium activity in 3D neuronal cultures as a read-out for network electric activity, which is abnormally increased in CDK5L-deficient neurons [ 125 ]. CDKL5 gene encodes for a serine/threonine kinase highly expressed in the central nervous system.…”
Section: Paving the Way: Rare Genetic Diseasesmentioning
confidence: 99%